Supranational Governance in Changing Societies of European Union in the Last Decade - WARSITO, TULUS (Universitas Muhammadiyah Yogyakarta, 2013)
As a supranational organization The European Union (EU) seems to compete the UNâ€™s reputations.UNO has more members since its scope is worldly, but UN does not issue its own currency while EUhas Euro. The Euro is the second largest reserve currency as well as the second most traded currencyin the world after the United States dollar. The currency is also used in a further many Europeancountries and consequently used daily by some 332 million Europeans. Additionally, over 175 millionpeople worldwide - including 150 million people in Africa - use currencies which are pegged to theEuro. No other transnational organization has such a specific currency. Although not as a unifiedmilitary conventional power, EU has such a â€œBattlegroupsâ€ initiative, each of which is planned to beable to deploy quickly about 1500 personnel. EU forces have been deployed on peacekeeping missionsfrom Africa to the former Yugoslavia and the Middle East. EU military operations are supported by anumber of bodies, including the European Defense Agency, European Union Satellite Centre and theEuropean Union Military Staff. In an EU consisting of 27 members, substantial security and defensecooperation is increasingly relying on great power cooperation.Despite those organizational strengths,only 27 of 57 European states are members of EU. And only 17 of 27 EU state members are usingEuro is their official currency. One prominent EU member like British stay tough with their ownPound-sterling.This paper is set to learn more about: why as a Europe continent based organization,EU state members are still less than half of European states? And why only 17 EU state members areusing Euro as their official currency?